Albiflorin inhibits inflammation to improve liver fibrosis by targeting the CXCL12/CXCR4 axis in mice - Meng, Lingjie; Lv, Huijing; Liu, Anli; Cao, Qian; Du, Xinyi; Li, Chengjin; Li, Qinggui; Luo, Qingqing; Xiao, Yi (Frontiers in Pharmacology, 2025)
Liver fibrosis is a common pathological feature of chronic hepatic injury that currently lacks effective therapeutic interventions. Albiflorin (ALB), a pinane-type monoterpene derived from Paeonia lactiflora Pall, has notable anti-inflammatory and hepatoprotective effects. However, the potential role of ALB against liver fibrosis is largely unknown. In this study, we discovered that ALB significantly inhibited CCl4-induced liver fibrosis in mice. This was evidenced by improvements in liver and kidney function indexes, fibrosis indicators, and histopathological findings. In vitro studies also showed that ALB inhibited TGF-β1-induced LX-2 cell activation and reduced the expression of α-SMA and collagen I. Additionally, we found that ALB mitigates inflammation and ameliorates liver fibrosis by targeting the CXCL12/CXCR4 axis, as confirmed using the CXCR4 inhibitor AMD3100 in CCl4-treated mice. Notably, combining ALB with metformin (MET) enhanced the inhibition of liver fibrosis progression. These findings highlight that ALB exerts anti-liver fibrosis effects by targeting the CXCL12/CXCR4 axis, underscoring its potential as a standalone treatment or as an adjuvant therapy.